2009
DOI: 10.1177/104063870902100409
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cervidpoxvirus Isolates from Oregon, California, and Eastern Canada

Abstract: Abstract. The present report describes the analysis of 4 Deerpox virus isolates from California, Oregon, and Ontario, Canada. All 4 isolates were associated with cutaneous crusting lesions. Examination of selected samples by electron microscopy demonstrated that the viruses were morphologically similar to orthopoxviruses. Phylogenetic analysis of the A21 gene, which is found in all poxviruses, indicated that the 4 isolates form a lineage distinct from other members except for those belonging to the genus Cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…The viruses belonging to the genus Deerpoxvirus (DPV) are responsible for non-parapoxviruslike infections in the members of two subfamilies of cervids, American deer (Odocoileinae) and reindeer (Rangiferinae). These viruses, resembling orthopoxviruses in shape, have been reported in North America in wild mule deer (Odocoileus hemionus) in Wyoming (2), black-tailed deer (O. h. columbianus) (3) and pudu (Pudu puda) (4) in California, in wild cervid species in the Northwest Pacific (5), in farmed white-tailed deer in Mississipi (6) and in a goitered gazelle (Gazella subgutturosa) (7). The first genome sequence of Mule Deerpoxvirus (MDPV), from a farmed white-tailed deer fawn in Florida, has been recently published by Sayler et al (8).…”
Section: Introductionmentioning
confidence: 92%
“…The viruses belonging to the genus Deerpoxvirus (DPV) are responsible for non-parapoxviruslike infections in the members of two subfamilies of cervids, American deer (Odocoileinae) and reindeer (Rangiferinae). These viruses, resembling orthopoxviruses in shape, have been reported in North America in wild mule deer (Odocoileus hemionus) in Wyoming (2), black-tailed deer (O. h. columbianus) (3) and pudu (Pudu puda) (4) in California, in wild cervid species in the Northwest Pacific (5), in farmed white-tailed deer in Mississipi (6) and in a goitered gazelle (Gazella subgutturosa) (7). The first genome sequence of Mule Deerpoxvirus (MDPV), from a farmed white-tailed deer fawn in Florida, has been recently published by Sayler et al (8).…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, Afonso et al (2005) found distinct genetic differences between the two isolates studied, suggesting multiple strains of virus within the species. This has been further supported by partial characterization of three Odocoileus hemionus origin isolates in our laboratory (Moerdyk-Schauwecker et al, 2009). Therefore it is likely that some strains will be more virulent than others and that these limited transmission studies only begin to define the range of clinical disease that DPV may induce.…”
Section: Discussionmentioning
confidence: 62%
“…The identity of the virus could not be established at that time. However, our research indicates that this virus is a member of the recently named Cervidpoxvirus genus (Moerdyk-Schauwecker et al, 2009). A novel poxvirus, measuring 245 3 200 nm has also been linked to cutaneous, ocular, and upper alimentary tract lesions in captive pudu, (Pudu puda), a cervid species native to South America (Junge et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This isolate was propagated and titered in Vero cells as previously described (Moerdyk-Schauwecker et al, 2009) for use in a standard serum neutralization (SN) plaque assay.…”
mentioning
confidence: 99%